ЖАРТАС ҚАЗТАМАҒЫ (GERANIUM SAXATILE KAR ET. KIR.) ӨСІМДІГІНІҢ ЖЕРАСТЫ ВЕГЕТАТИВТІК МҮШЕСІНІҢ ЖАСТЫҚ КЕЗЕҢДЕРГЕ САЙ ҚАЛЫПТАСУ ЕРЕКШЕЛІГІ (Experimental biology, 2011)
In this article was studied the vegetable organs natural formation over ground if agencys plant of Geranium saxatile Kar et. Kir
Keywords: Geranium saxatile